Investigating the Effect of Volatiles on Sub-23 nm Particle Number Measurements for a Downsized GDI Engine with a Catalytic Stripper and Digital Filtering - Sebastian A. Pfau; Ephraim Haffner-Staton; Antonino La Rocca; Alasdair Cairns (Fuels, 2022)
Recent efforts of both researchers and regulators regarding particulate emissions have focused on the contribution and presence of sub-23 nm particulates. Despite being previously excluded from emissions legislation with the particle measurement programme (PMP), the latest regulatory proposals suggest lowering the cut-off sizes for counting efficiencies and the use of catalytic strippers to include solid particles in this size range. This work investigated particulate emissions of a 1.0 L gasoline direct injection (GDI) engine using a differential mobility spectrometer (DMS) in combination with a catalytic stripper. Direct comparison of measurements taken with and without the catalytic stripper reveals that the catalytic stripper noticeably reduced variability in sub-23 nm particle concentration measurements. A significant portion of particles in this size regime remained (58–92%), suggesting a non-volatile nature for these particles. Digital filtering functions for imposing defined counting efficiencies were assessed with datasets acquired with the catalytic stripper; i.e., particle size distributions (PSDs) with removed volatiles. An updated filtering function for counting efficiency thresholds of d65 = 10 nm and d90 = 15 nm showed an increase in particulate numbers between 1.5% and up to 11.2%, compared to the closest previous digital filtering function. However, this increase is highly dependent on the underlying PSD. For a matrix of operating conditions (1250 to 2250 rpm and fast-idle to 40 Nm brake torque), the highest emissions occurred at fast-idle 1250 rpm with <semantics>1.93<mtext> </mtext>×<mtext> </mtext>108<mtext> </mtext>#/cm3</semantics> using the updated filtering function and catalytic stripper. This setup showed an increase in particulate number of +27% to +390% over the test matrix when compared to DMS measurements without the catalytic stripper and applied counting efficiency thresholds of d50 = 23 nm and d90 = 41.